Analysis of the effect of grouting parameters on pile-soil interaction of grouted piles - Shi, Si-Si; Wan, Zhi-Hui; Hu, Tao; Qian, Xiao-Nan; Duan, Chang; Qi, Kai (Frontiers in Earth Science, 2023)
Reasonable control of grouting parameters was the key to improving the pile-soil interaction. However, quantitative analysis on the effect of grouting parameters on the pile-soil interaction was still lacking. This article developed an intelligent post-grouting system for precise control and quantitative analysis of grouting parameters. The conventional preparation method for shear tests were improved in this article. By changing the normal stress of the pile-soil interface during grouting, the test sample could simulate the grout distribution of the pile-soil interface at different depths. Through the improved experimental methods, a more accurate analysis of the mechanism for the pile-soil interaction was achieved. And the effectiveness of the intelligent post-grouting system was further verified by the case application. The results indicated that increasing the grout volume could improve the interface shear strength when the normal stress and grouting pressure were constant. This improvement effect caused by increasing grout volume decreased when the normal stress was high. Increasing the grouting pressure increased the interface shear strength when the normal stress and the grout volume remained constant. This improvement effect caused by increasing grouting pressure decreased when the grout volume was small. By appropriately controlling the two grouting parameters, the cohesion and the shear strength of the pile-soil interface were increased by 5.8–18.8 times and 1.16–2.91 times, respectively. The results indicated that the intelligent post-grouting system could accurately control the grouting parameters and effectively improve the pile-soil interaction of bored piles. The intelligent post-grouting system effectively reduced geotechnical engineering risks and improved the bearing capacity of pile.